Bayesian machine learning identifies precipitation as a key predictor in alpine soil carbon spatial structuring - Zhaoqi Wang; Sheng Yu; Xiaotao Huang; Ting Zhou; Haichen Zhang; Yangyang Liu; Guiling Wu; Kai Zheng; Mingxue Xiang; Tao Ma; Dan Liu; Yongkang Lu (Soil and Tillage Research, 2026)

PmFREP1 exhibits antibacterial activity and bacterial agglutination in Pinctada fucata martensii - Qiyuan Zhang; Chuanjie Liu; Haiying Liang; Junqin Huang; Lining Ma; Guiling Yin (Fish & Shellfish Immunology, 2026)

The study of intestinal toxicity induced by gossypol acetic acid and the mechanism using zebrafish model and network toxicology - Hanxue Zhao; Yuxin Wang; Guoliang Zhang; Yudi Jing; Fangzhen Li; Xiqiang Chen; Kechun Liu; Guiling Chen; Rongchun Wang (Toxicology and Applied Pharmacology, 2026)

Rapid biodegradation of glyphosate by plant growth-promoting Ochrobactrum sp. Y3: Degradation kinetics, metabolic pathways and environmental bioremediation - Shichen Dai; Chenxi Yan; Mingqiu Liu; Yuxi Sun; Keyi Wang; Guiling Si; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2026)

Lithium enrichment in geothermal systems of the Tibetan Plateau: A coupled machine learning–geochemistry framework for mechanism and prediction - Shuaichao Wei; Wei Zhang; Guiling Wang; Feng Liu; Feng Tian; Xiaoxue Yan; Ruoxi Yuan; Zengrun Yang; Yong Fu (Earth-Science Reviews, 2026)

Identifying the role of Zr4+ cations in enhancing oxygen migration of cerium-zirconium oxides for two-step thermochemical CO2 splitting - Shuaijie Xu; Yanxin Liu; Xi Cao; Guiling Xu; Changsheng Bu (Fuel, 2026)

Enhanced glyphosate biodegradation by heavy metal-tolerant microbial consortium QLBS in co-contaminated environment: Kinetics and metabolic pathways - Zeren Li; Mengyi Chen; Ziye Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Haoran Song; Huijie Zhou; Zhenyu Zhang; Bin Liang; Sandhya Mishra; Mohamed A. Ghorab; et al. (Journal of Cleaner Production, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Optimizing geothermal reservoir performance: A hybrid DFN-EPM simulation approach for fracture convection equivalence and enhanced production forecasting - Honglei Shi; Chuan Lu; Kefei Sun; Guiling Wang; Yaning Wang; Lu Liu; Jun Gao; Yunjie Wei (Geothermics, 2026)

Soil Li-Rb-Cs-B as near-surface tracers of shallow-buried high-temperature geothermal systems: A case study from the Yangbajing geothermal field, Tibet Plateau - Wanli Wang; Guiling Wang; Yajuan Duan; Linxiao Xing; Wei Zhang; Jiayi Zhao; Honglei Shi; Lu Liu; Yanliang Tian; Sonam Tsering (Geothermics, 2026)

Covalently bonded amino-functionalized ZIF-8 on Cu2O for photocatalytic reduction of low-concentration CO2 - Jinke Li; Zhenbo Zhang; Guiling Liu; Hao Shi; Jingru Wang; Jiayi Wan; Tong Bian; Huijun Yu (Chemical Engineering Journal, 2026)

Tide-triggered N2O emission dynamics in saltmarsh wetlands of the Yangtze Estuary: Significance of N2O consumption - Manping Zhang; Chenchen Lixiang; Jianli Wen; Shanshan Sun; Xushun Gu; Shaoxuan Ding; Shengbing He; Guiling Liu (International Biodeterioration & Biodegradation, 2026)

Optimization of coal-based solid fuels for direct carbon fuel cells by chemical treatments - Yue Ding; Xuan Zhang; Shuyue Liu; Jinling Yin; Xianchao Wang; Jing Zhao; Qing Wen; Jiaxin Yao; Guiling Wang (Fuel, 2026)

Differences in Volatile Composition and Expression of Genes Involved in Terpenes Biosynthesis in Hemerocallis Species - Wenjie Gao; Yuyang Li; Xingran Kou; Qinfei Ke; Feng Chen; Guiling Liu; Qingran Meng (Journal of Plant Growth Regulation, 2026)

Multiple-level fault controlled hydrothermal system in Huangshadong, Southeast China: Insights from coupled geophysical and geochemical investigations - Lu Liu; Xianan Qin; Zheng’an Wei; Min Zhang; Honglei Shi; Xiting Long; Wenjing Lin; Mingxiang Qiu; Guiling Wang; Shihua Qi; Fei Liu (Geothermics, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Bacillus subtilis as a powerful weapon in the removal of environmental pollutants - Mingqiu Liu; Wen-Juan Chen; Guiling Si; Chenxi Yan; Haoran Song; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Fibroblast Growth Factor 8 Suppresses Neurotoxic Astrocytes and Alleviates Neuropathic Pain via Spinal FGFR3 Signaling - Huizhu Liu; Lanxing Yi; Guiling Li; Kangli Wang; Hongsheng Wang; Yuqiu Zhang; Benlong Liu (Neuroscience Bulletin, 2025)
Astrocytes in the spinal dorsal horn (SDH) exhibit diverse reactive phenotypes under neuropathic conditions, yet the mechanisms driving this diversity and its implications in chronic pain remain unclear. Here, we report that spared nerve injury (SNI) induces marked upregulation of both complement component 3 (C3⁺, A1-like) and S100 calcium-binding protein A10 (S100A10⁺, A2-like) astrocyte subpopulations in the SDH, with elevated microglial cytokines including interleukin-1α, tumor necrosis factor-α, and complement component 1q. Transcriptomic, immunohistochemical, and Western blot analyses reveal co-activation of multiple reactive astrocyte states over a unidirectional shift toward an A1-like phenotype. Fibroblast growth factor 8 (FGF8), a neuroprotective factor via FGFR3, mitigated microglia-induced C3⁺ astrocyte reactivity in vitro and suppressed spinal C3 expression and mechanical allodynia following intrathecal administration in SNI mice. These findings reveal a microglia–astrocyte signaling axis that promotes A1 reactivity and position FGF8 as a promising therapeutic candidate for neuropathic pain by modulating astrocyte heterogeneity.

Biodegradation of the widely used amide herbicides: Microbial resources, catabolic pathways and molecular mechanisms - Guiling Si; Quanhong Zhang; Mingqiu Liu; Wen-Juan Chen; Yuting Tong; Parul Chaudhary; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

Enhancing geothermal energy recovery in Yangbajing: The role of natural and artificial fracture connectivity in EGS performance - Honglei Shi; Guiling Wang; Chuan Lu; Wanli Wang; Lu Liu; Yunjie Wei (Geothermics, 2025)

High-value utilization of volcanic rock as NH3-SCR denitration catalyst loaded with Mn: denitration effect and mechanism - Bo Song; Zhenxing Shen; Qingzhu Tian; Guiling Zhou; Qin Peng; Hao Fan; Jia Liu (Environmental Research, 2025)

A SERS-active microneedle array for rapid and minimally invasive lactic acid detection - Xinyu Sun; Kequan Chen; Yang Wang; Zhiwei Zhang; Jinfeng Lin; Guiling Liu; Dianhuai Meng; Jian Dong; Yan Huang (Analytica Chimica Acta, 2025)

Dual-modal aptamer/CRISPR-Cas12a biosensor with Fe-C-N@Au nanozyme for simultaneous detection of azithromycin and macrolide resistance genes and degradation of azithromycin - Guiling Liu; Zongwu Meng; Wanshu Zheng; Anqi Qiu; Yuan Tian; Zerun Zhang; Tao Zhang; Pian Wu; Ping Ding (Journal of Hazardous Materials, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Responses of June Precipitation in Eastern China to Late Spring Soil Temperature Anomaly over the Qinghai–Xizang Plateau: Results from a Regional Climate Model - Wenchao Wang; Miao Yu; Yongkang Xue; Jianping Tang; Weiguang Liu; Guiling Wang; Jie Zhang; Hong Wu (Journal of Meteorological Research, 2025)

3-Phenoxybenzoic Acid Induces Neuronal Pentraxin 2 to Upregulate Complement Activity and Promotes Microglia-Mediated Neuronal Synaptic Damage - Guiling Hu; Kaidong Wang; Chenyang Wu; Qi Liu; Qianrong Zhang; Ai Qi; Min Huang (Journal of Molecular Neuroscience, 2025)

C22-Ceramide Derived from Marine Microalgae Emiliania huxleyi Induces Melanosomal Autophagy via JNK/c-Jun Signaling Pathway in Mouse B16 Melanoma Cells - Jiyue Wan; Hui Ma; Yuxuan Xu; Shumiao Zhang; Jian Li; Guiling Li; Shiying Huang; Xiaotong Ye; Zhengxiao Zhang; Jingwen Liu (Journal of Ocean University of China, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Genetically engineered Bacillus subtilis-derived extracellular vesicles Alleviates Ulcerative colitis by restoring intestinal barrier and regulating gut microbiota - Jiali Chen; Chaozhi Wei; Chunqiang Pan; You Wei; Baoxian Li; Tao Liu; Xiao Wang; Zhengshun Wen; Yao Zhao; Mengyu Zhang; Jintao Cheng; Yuanxiang Jin; et al. (Chemical Engineering Journal, 2025)

Resource utilization of red mud with biochar to prepare high-efficiency denitration catalysts - Bo Song; Zhenxing Shen; Zitong Wang; Guiling Zhou; Qin Peng; Hao Fan; Jia Liu (Journal of Cleaner Production, 2025)

Evaluating the effects of intrinsic and isolated arabinoxylans on human gut microbiota and short-chain fatty acids: A systematic review and meta-analysis - Changcan Feng; Chenxi Cai; Edward C. Deehan; Shanshan Jiang; Mingyue Yang; Zhongming Weng; Jiahui Long; Guiling Li; Jian Li; Jingwen Liu; Zhengxiao Zhang (Trends in Food Science & Technology, 2025)

Unveiling the hydrolase Oph2876 mediated chlorpyrifos degradation mechanism in Pseudomonas nitroreducens and its potential for environmental bioremediation - Haoran Song; Wen-Juan Chen; Shao-Fang Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Hazardous Materials, 2025)

Regulation and response of heterotrophic bacterial production to environmental changes in marginal seas of the Western Pacific Ocean - Qiao Liu; Jinyan Wang; Xiao-Jun Li; Ni Meng; Gui-Peng Yang; Guiling Zhang; Guang-Chao Zhuang (Global and Planetary Change, 2025)

Removal of alachlor from the water/soil environments: The significance of microbial remediation and its biochemical mechanisms - Zeren Li; Mengyi Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Water Process Engineering, 2024)

Three dietary phenols from pickled radish improve uric acid metabolism disorder in hyperuricemia mice associated with the altered gut microbiota composition - Xiaoze Liu; Lingyu Zhang; Daren Wu; Jingwen Liu; Guiling Li; Zhengxiao Zhang; Jian Li (Food Bioscience, 2024)

First record of the sap beetle Phenolia picta invading Eastern honey bee (Apis cerana) (Hymenoptera, Apidae) colonies - Lin Du; Wenbin Liu; Xiaoshun Chen; Jinge Licao; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

Hydrogeochemistry of geothermal water in Huangshadong and adjacent areas of Guangdong province: Implications for water-rock interaction - Lu Liu; Guiling Wang; Yalu Li; Zhengan Wei; Wenjing Lin; Xianan Qin; Min Zhang; Shihua Qi; Xiting Long (Geothermics, 2024)

Exploring the dynamic behaviors of five pesticides in lettuce: Implications for consumer health through field and modeling experiments - Yanhua Wang; Panpan Liu; Guiling Yang; Fang Shu; Chen Chen (Food Chemistry, 2024)

Preparation and identification of antioxidant peptides from Quasipaa spinosa skin through two-step enzymatic hydrolysis and molecular simulation - Daren Wu; Yuanhao Cao; Dejin Su; Emad Karrar; Lingyu Zhang; Chaoxiang Chen; Ning Deng; Zhengxiao Zhang; Jingwen Liu; Guiling Li; Jian Li (Food Chemistry, 2024)

Distribution, seasonal variation and influencing factors of total dissolved inorganic arsenic in the middle and lower reaches of the Yellow River - Mengyao He; Jingling Ren; Jiaqi Liu; Sumei Liu; Guiling Zhang; Guodong Song (Marine Pollution Bulletin, 2024)

Focus on the nonlinear infiltration process in deep vadose zone - Yujiang He; Yanyan Wang; Ying Liu; Borui Peng; Guiling Wang (Earth-Science Reviews, 2024)

Structure-activity relationships of antimicrobial phenolic derivatives from Phyllanthus emblica against Streptomyces scabies - Xiuna Wu; Daren Wu; Jiahao Yuan; Lingyu Zhang; Jingwen Liu; Guiling Li; Li Wang; Jian Li (Food Bioscience, 2024)

A review of cumulative risk assessment of multiple pesticide residues in food: Current status, approaches and future perspectives - Mengxue Yang; Yihan Wang; Guiling Yang; Yanhua Wang; Fengquan Liu; Chen Chen (Trends in Food Science & Technology, 2024)

Coupled THMC modeling on chemical stimulation in fractured geothermal reservoirs - Haoran Xu; Guihong Liu; Zhihong Zhao; Feng Ma; Guiling Wang; Yuedu Chen (Geothermics, 2024)

Vitamin a supplementation during pregnancy in shaping child growth outcomes: A meta-analysis - Guiling Ma; Yanting Chen; Xiangdong Liu; Yao Gao; Jeanene M. Deavila; Mei-Jun Zhu; Min Du (Critical Reviews in Food Science and Nutrition, 2023)

Identification of flavonoids in Anoectochilus roxburghii and in vitro inhibition of key enzymes relevant to metabolic syndrome - Jiahao Yuan; Xiuna Wu; Emad Karrar; Lingyu Zhang; Jingwen Liu; Guiling Li; Chaoxiang Chen; Zhengxiao Zhang; Daren Wu; Jian Li (Food Bioscience, 2023)

Study on the Role of Mitophagy Receptor PHB2 in Doubly Uniparental Inheritance of Hyriopsis cumingii - Yayu Wang; Xiaoyue Zhu; Yang Gu; Zongyu Liu; Yingrui Mao; Xiaojun Liu; Zhiyi Bai; Guiling Wang; Jiale Li (Marine Biotechnology, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Characterization of the sphingolipid profiling of Emiliania huxleyi against virus infection - Jingwen Liu; Jingjing Gao; Enquan Zhang; Hanrui Jiang; Guiling Li; Jian Li; Jun Zeng; Daren Wu (Journal of Oceanology and Limnology, 2023)

A Responsive Feeding Questionnaire Based on Self-Determination Theory for Caregivers of Chinese Toddlers - Yan Liu; Guiling Yu; Zhihui Li; Yan Kong; Rui Yang; Chunlan Yin; Xiaodi Sun (Journal of Nutrition Education and Behavior, 2023)

Larger bees facilitate the deposition of oilseed rape pollen (Brassica napus L.) - Hongcai Chang; Zhijun Wei; Ran Liu; Guiling Ding; Jun Li; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2023)

Tacrolimus improved the pregnancy outcomes of patients with refractory recurrent spontaneous abortion and immune bias disorders: a randomized controlled trial - Juan Liu; Meiqin Li; Jinhua Fu; Guiling Yuan; Ning Li; Yinghui Fu; Long Zhao (European Journal of Clinical Pharmacology, 2023)

Modulation of non-covalent wet adhesion and cohesion via proximally immobilized non-lysine pair structure - Pengxu Wang; Qing Liu; Wenliang Fu; Chao Zhang; Guiling Cai; Weiwei Xing; Hongliang Dai; Hongya Geng; Donggang Xu (Chemical Engineering Journal, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Benthic nitrogen cycling in the deep ocean of the Kuroshio Extension region - Haoming Xu; Guodong Song; Siqi Yang; Ruosi Zhu; Guiling Zhang; Sumei Liu (Frontiers in Marine Science, 2022)
Benthic nitrogen cycling, including nitrification, N-loss, and other nitrogen transformations, plays a crucial role in the marine nitrogen budget. However, studies on benthic nitrogen cycling mainly focus on marginal seas, while attention to the deep ocean, which occupies the largest area of the seafloor, is severely lacking. In this study, we investigate the benthic nitrogen cycling in the Kuroshio Extension region (KE) of the northwest Pacific Ocean at water depths greater than 5,000 m through 15 N enrichment slurry incubation and pore-water dissolved oxygen and inorganic nitrogen profiles. The slurry incubation indicates nitrification is the predominant process in benthic nitrogen cycling. The potential nitrification rates are nearly an order of magnitude higher than dissimilatory nitrate reduction. Nitrification and total N-loss flux estimated from pore-water nitrate and ammonium profiles are 6–42 and 5–30 μmol N m −2 d −1 , respectively. Generally, anammox is the predominant N-loss process in KE sediment. The temperature gradient experiment indicates that the optimum temperature for anammox and denitrification is 13 and 41°C, respectively, partially explaining anammox as the dominant process for deep-ocean benthic N-loss. Both the low concentration of ammonium in pore-water and the discrepant results between anoxic incubation amended with 15 NO 3 − and 15 NH 4 + + 14 NO 3 − suggest that ammonium is another limiting factor for benthic anammox. N-loss activity gradually declines with the distance from the Oyashio–Kuroshio transition zone. However, nitrification has the opposite trend roughly. This reveals that the sediment in KE transfers from nitrate sink to source from north to south. This trend is mainly caused by the variation of primary production and the supplement of active organic matter, which is the energy source for microbes and the potential source for ammonium through remineralization. Overall, our results highlight temperature and ammonium as two limiting factors for deep-ocean benthic N-loss and also exhibit a tight coupling relationship between pelagic primary production and the benthic nitrogen cycle in KE.

G-CSF promotes the viability and angiogenesis of injured liver via direct effects on the liver cells - Zifeng Liu; Guiling Zhang; Jing Chen; Jingjing Tong; Hongmin Wang; Jing Chen; Dong Yang; Jinhua Hu (Molecular Biology Reports, 2022)
Background Presently, liver transplantation is the only treatment strategy for liver failure (LF). Although granulocyte-colony stimulating factor (G-CSF) exhibits protective functions in LF, it is not clear whether it directly affects the liver cells. Methods and Results We established an injured liver cell model and observed that G-CSF treatment promoted cell viability and enhanced Ki67 and VEGF-A expression. Thereafter, human umbilical vein endothelial cells (HUVECs) were cultured in a conditioned medium collected from the G-CSF-treated injured liver cells. HUVECs’ proliferation and tubule formation were promoted. Furthermore, in an injured liver mouse model, confirmed via haematoxylin–eosin staining, we evaluated serum alanine aminotransferase activity, Ki67 expression, and microvessel density (MVD). G-CSF treatment significantly relieved liver injury, upregulated Ki67 expression, and enhanced MVD in the injured mouse liver tissue. Additionally, AKT and ERK signal targets were explored, and it was demonstrated that the effects of G-CSF on injured liver cells were mediated through the AKT and ERK signalling pathways. Conclusions G-CSF promotes injured liver viability and angiogenesis by directly affecting injured liver cells via the AKT and ERK signalling pathways. These findings improve our understanding of the role of G-CSF in recovery from LF.

Coupled Thermo-Hydro-Mechanical Modeling on the Rongcheng Geothermal Field, China - Feng Ma; Guihong Liu; Zhihong Zhao; Haoran Xu; Guiling Wang (Rock Mechanics and Rock Engineering, 2022)

Molecular characteristics and pathogenicity of an equid alphaherpesvirus 1 strain isolated in China - Yue Hu; Qinrui Jia; Jianhua Liu; Wencheng Sun; Zilei Bao; Chuanzhong Che; Guiling Wu; Bin Fan; Jarhen; Duoliang Ran (Virus Genes, 2022)

Sensitivity of Typhoon Lingling (2019) simulations to horizontal mixing length and planetary boundary layer parameterizations - Siqi Chen; Feng Xu; Yu Zhang; Guiling Ye; Jianjun Xu; Chunlei Liu (Frontiers of Earth Science, 2022)

LncRNA NEAT1 contributes to the acquisition of a tumor like-phenotype induced by PM 2.5 in lung bronchial epithelial cells via HIF-1α activation - Pan Jiang; Shengyu Hao; Liang Xie; Guiling Xiang; Weiping Hu; Qinhan Wu; Zilong Liu; Shanqun Li (Environmental Science and Pollution Research, 2021)

Using triple oxygen isotopes and oxygen-argon ratio to quantify ecosystem production in the mixed layer of northern South China Sea slope region - Zhuoyi Zhu; Jun Wang; Guiling Zhang; Sumei Liu; Shan Zheng; Xiaoxia Sun; Dongfeng Xu; Meng Zhou (Acta Oceanologica Sinica, 2021)

Flavonoids improve drought tolerance of maize seedlings by regulating the homeostasis of reactive oxygen species - Baozhu Li; Ruonan Fan; Guiling Sun; Ting Sun; Yanting Fan; Shenglong Bai; Siyi Guo; Shiquan Huang; Jiong Liu; Hui Zhang; Pengtao Wang; Xiaohong Zhu; et al. (Plant and Soil, 2021)
Background and aims As drought threatens the yield and quality of maize ( Zea mays L.), it is important to dissect the molecular basis of maize drought tolerance. Flavonoids, participate in the scavenging of oxygen free radicals and alleviate stress-induced oxidative damages. This study aims to dissect the function of flavonoids in the improvement of maize drought tolerance. Methods Using far-infrared imaging screening, we previously isolated a drought overly insensitivity ( doi ) mutant from an ethyl methanesulfonate (EMS)-mutagenized maize library and designated it as doi57 . In this study, we performed a physiological characterization and transcriptome profiling of doi57 in comparison to corresponding wild-type B73 under drought stress. Results Under drought stress, doi57 seedlings displayed lower leaf-surface temperature (LST), faster water loss, and better performance in growth than B73. Transcriptome analysis reveals that key genes involved in flavonoid biosynthesis are enriched among differentially expressed genes in doi57 . In line with these results, more flavonols and less hydrogen peroxide (H 2 O 2 ) were accumulated in guard cells of doi57 than in those of B73 with the decrease of soil water content (SWC). Moreover, the capacity determined from doi57 seedling extracts to scavenge oxygen free radicals was more effective than that of B73 under the drought treatment. Additionally, doi57 seedlings had higher photosynthetic rates, stomatal conductance, transpiration rates, and water use efficiency than B73 exposed to drought stress, resulting in high biomass and greater root/shoot ratios in doi57 mutant plants. Conclusion Flavonoids may facilitate maize seedling drought tolerance by lowering drought-induced oxidative damage as well regulating stomatal movement.

Transformation of coccolithophorid Emiliania huxleyi harboring a marine virus (Coccolithoviruses) serine palmitoyltransferase (SPT) gene by electroporation - Weicong Cai; Xueting Wang; Jinjing Su; Jian Li; Jun Zeng; Guiling Li; Jingwen Liu (Journal of Oceanology and Limnology, 2021)

Response of benthic nitrogen cycling to estuarine hypoxia - Guodong Song; Sumei Liu; Jing Zhang; Zhuoyi Zhu; Guiling Zhang; Hannah K. Marchant; Marcel M. M. Kuypers; Gaute Lavik (Limnology and Oceanography, 2021)
The effects of bottom water oxygen concentration on sediment oxygen uptake, oxygen penetration depth, nitrate and ammonium fluxes, anammox, denitrification, dissimilatory nitrate reduction to ammonium, nitrification, and mineralization were investigated off the Changjiang estuary and its adjacent East China Sea, by combining a seasonal comparison with three artificially induced bottom water oxygen conditions (oxic, ambient, and severe hypoxia). A 50% decrease in in‐situ bottom water oxygen concentrations between May and August, led to decreases in the average sediment oxygen uptake and oxygen penetration depth by 23% and 29%, respectively. Anammox rates decreased by a factor of 2.5, and the relative contribution of anammox to the total benthic N‐loss decreased from 20% to 7.4%. However, denitrification rates increased, leading to an overall benthic N‐loss rate of 0.85 mmol N m −2 d −1 . At the same time, an increasing contribution of dissimilatory nitrate reduction to ammonium to total nitrate reduction led to higher recycling of inorganic nitrogen during hypoxia in August. Under artificially induced conditions of severe hypoxia, there was a sharp decrease in both sediment oxygen uptake and benthic N‐loss rates by 88% and 38%, respectively. Nitrate and ammonium fluxes showed complex behavior at different sites which could be related to the repression of sedimentary nitrification below a bottom water oxygen threshold of 9.7 μ M and increasing dissimilatory nitrate reduction to ammonium. Taken together, our results indicate that changes in benthic nutrient cycling under seasonal hypoxia enhance the retention of both organic and inorganic nitrogen, thereby exacerbating oxygen deficiency.

High-resolution distributions of O 2 / Ar on the northern slope of the South China Sea and estimates of net community production - Chuan Qin; Guiling Zhang; Wenjing Zheng; Yu Han; Sumei Liu (Ocean Science, 2021)
The dissolved oxygen-to-argon ratio (O2∕Ar) in the oceanic mixed layer has been widely used to estimate net community production (NCP), which is the difference between gross primary production and community respiration; it is a measure of the strength of the biological pump. In order to obtain the high-resolution distribution of NCP and improve our understanding of its regulating factors in the slope region of the northern South China Sea (SCS), we conducted continuous measurements of dissolved O2, Ar, and CO2 with membrane inlet mass spectrometry (MIMS) during two cruises in October 2014 and June 2015. An overall autotrophic condition was observed in the study region in both cruises with an average Δ(O2∕Ar) of 1.1 % ± 0.9 % in October 2014 and 2.7 % ± 2.8 % in June 2015. NCP was on average 11.5 ± 8.7 mmol C m−2 d−1 in October 2014 and 11.6 ± 12.7 mmol C m−2 d−1 in June 2015. Correlations between dissolved inorganic nitrogen (DIN), Δ(O2∕Ar), and NCP were observed in both cruises, indicating that NCP is subject to the nitrogen limitation in the study region. In June 2015, we observed a rapid response of the ecosystem to the episodic nutrient supply induced by eddies. Eddy-entrained shelf water intrusion, which supplied large amounts of terrigenous nitrogen to the study region, promoted NCP in the study region by potentially more than threefold. In addition, upwelling brought large uncertainties to the estimation of NCP in the core region of the cold eddy (cyclone) in June 2015. The deep euphotic depth in the SCS and the absence of correlation between NCP and the average photosynthetically available radiation (PAR) in the mixed layer in the autumn indicate that light availability may not be a significant limitation on NCP in the SCS. This study helps us to understand the carbon cycle in the highly dynamic shelf system.

Projecting the future vegetation–climate system over East Asia and its RCP-dependence - Weiguang Liu; Guiling Wang; Miao Yu; Haishan Chen; Yelin Jiang; Meijian Yang; Ying Shi (Climate Dynamics, 2020)

Variations in Dissolved Methane in the Yellow Sea During the Spring Algal Blooms of 2009 - Wangwang Ye; Guiling Zhang; Peipei Li; Feng Zhou; Chenggang Liu (Journal of Ocean University of China, 2019)

Quality Control and Evaluation of the Observed Daily Data in the North American Soil Moisture Database - Weilin Liao; Dagang Wang; Guiling Wang; Youlong Xia; Xiaoping Liu (Journal of Meteorological Research, 2019)

Virus-induced apoptosis and phosphorylation form of metacaspase in the marine coccolithophorid Emiliania huxleyi - Jingwen Liu; Weicong Cai; Xian Fang; Xueting Wang; Guiling Li (Archives of Microbiology, 2018)

Influence of a water regulation event on the age of Yellow River water in the Bohai - Zhen Li; Haiyan Wang; Xinyu Guo; Zhe Liu; Huiwang Gao; Guiling Zhang (Journal of Ocean University of China, 2017)

Estimated influence of urbanization on surface warming in Eastern China using time‐varying land use data - Weilin Liao; Dagang Wang; Xiaoping Liu; Guiling Wang; Jinbao Zhang (International Journal of Climatology, 2017)
We examine the urban effect on surface warming in Eastern China, where a substantial portion of the land area has undergone rapid urbanization in the last few decades. Daily surface air temperature records during the period 1971–2010 at 277 meteorological stations are used to investigate temperature changes. Owing to urban expansion, some of the stations formerly located in rural areas are becoming increasingly influenced by urban environments. To estimate the effect of this urbanization on observed surface warming, the stations are dynamically classified into urban and rural types based on the land use data for four periods, i.e. 1980, 1990, 2000 and 2010. After eliminating the temperature trend bias induced by time‐varying latitudinal distributions of urban and rural stations, the estimated urban‐induced trends in the daily minimum and mean temperature are 0.167 and 0.085 °C decade −1 , accounting for 33.6 and 22.4% of total surface warming, respectively. The temperature difference between urban and rural stations indicates that urban heat island intensity has dramatically increased owing to rapid urbanization, and is highly correlated with the difference in fractional coverage of artificial surfaces between these two types of stations. This study highlights the importance of dynamic station classification in estimating the contribution of urbanization to long‐term surface warming over large areas.

Identification and characterization of a novel NAC-like gene in chrysanthemum (Dendranthema lavandulifolium) - Yanfang Yang; Kai Zhu; Jian Wu; Liqing Liu; Guiling Sun; Yanbiao He; Fadi Chen; Deyue Yu (Plant Cell Reports, 2016)

Quantifying the preferential flow by dye tracer in the North China Plain - Qinghua Wu; Chunlei Liu; Wenjing Lin; Meng Zhang; Guiling Wang; Fawang Zhang (Journal of Earth Science, 2015)

Large-scale analysis of protein phosphorylation in Populus leaves - Jinwen Liu; Deli Ning; Guiling Zhao; Yuxiang Cheng; Baichen Wang (Journal of Plant Biochemistry and Biotechnology, 2014)

Identification of QTLs for salt tolerance at germination and seedling stage of Sorghum bicolor L. Moench - Hailian Wang; Guiling Chen; Huawen Zhang; Bin Liu; Yanbing Yang; Ling Qin; Erying Chen; Yanan Guan (Euphytica, 2014)

Comparison of growth and pearl production in males and females of the freshwater mussel, Hyriopsis cumingii, in China - Yongchao Zhao; Zhiyi Bai; Longlong Fu; Yue Liu; Guiling Wang; Jiale Li (Aquaculture International, 2013)

Analysis on cDNA sequence, alternative splicing and polymorphisms associated with timing of puberty of Lin28B gene in goats - Guiling Cao; Qiuyue Liu; Mingxing Chu; Ran Di; Li Fang; Tao Feng; Ning Li (Molecular Biology Reports, 2013)

Programmed cell death is responsible for replaceable bud senescence in chestnut (Castanea mollissima BL.) - Guangpeng Wang; Zhihong Zhang; Dejun Kong; Qingxiang Liu; Guiling Zhao (Plant Cell Reports, 2012)

Molecular cytogenetic identification of a novel dwarf wheat line with introgressed Thinopyrum ponticum chromatin - Guiling Chen; Qi Zheng; Yinguang Bao; Shubing Liu; Honggang Wang; Xingfeng Li (Journal of Biosciences, 2012)

Characterization of the Hormone and Stress-Induced Expression of FaRE1 Retrotransposon Promoter in Strawberry - Ping He; Yue Ma; Hongyan Dai; Linguang Li; Yuexue Liu; He Li; Guiling Zhao; Zhihong Zhang (Journal of Plant Biology, 2012)

Integrating miRNA and mRNA expression profiles in response to heat stress-induced injury in rat small intestine - Jin Yu; Fenghua Liu; Peng Yin; Xiaoyu Zhu; Guiling Cheng; Nin Wang; An Lu; Weili Luan; Nuowei Zhang; Jiefeng Li; Kaijun Guo; Yulong Yin; et al. (Functional & Integrative Genomics, 2011)

Cycling of phosphorus in the Jiaozhou Bay - Xiaohong Qi; Sumei Liu; Jing Zhang; Jingling Ren; Guiling Zhang (Acta Oceanologica Sinica, 2011)

Assessment of the conventional molybdenum-blue and magnesium-induced coprecipitation procedures in phosphorus measurement in various aquatic environments - Sumei Liu; Yingfei Zhao; Jingling Ren; Jing Zhang; San Sun; Jie Jin; Guiling Zhang (Acta Oceanologica Sinica, 2010)